Devi - Mukhopādhyāẏa, Prabhātakumāra 1873-1932; Khan, Ali Akbar 1922-2009 (<<The>> Criterion Collection, 2021)
"A young woman is deemed a goddess when her father-in-law, a rich feudal land-lord, has a dream envisioning her as an avatar of Kali." [imdb.com
Original: Indien 1960
DVD special edition features: new 4k digital restoration ; new program featuring interviews with Sharmila Tagore and Soumitra Chatterjee recorded in 2013 ; new video essay by film scholar Meheli Sen ; new English subtitle translation ; plus: an essay by film critic Devika Girish
Bildformat 1.37:1
Keywords: Film; DVD-Video